Quantifying exhumation using compaction and vitrinite reflectance in the Southern Bonaparte Basin, North West Shelf, Australia. (December 2021) - Makuluni, Patrick; Johnson, Lukman Mobolaji; Hauser, Juerg; Langhi, Laurent; Clark, Stuart
Abstract: Rock fracture during exhumation can enhance hydrocarbon fluid migration through reservoir rocks but can also breach seal rocks and cause fluids to escape. Therefore, understanding the spatial and temporal distribution of exhumation within sedimentary basins can help optimize oil and gas systems targeting and help identify potential subsurface locations for CO2 storage. Structural, tectonic and stratigraphic studies suggest that the hydrocarbon-rich Bonaparte Basin of the Australian North West Shelf has undergone multiple episodes of exhumation since the Palaeozoic. However, the distribution of this exhumation and its correlation with the distribution of petroleum systems in the basin is not well established. In this work, we combine compaction and vitrinite reflectance analysis to estimate exhumation on selected boreholes, then model its temporal and spatial distribution within the southern Bonaparte Basin. The compaction and vitrinite reflectance analysis use porosity and paleotemperature data of sediments, respectively, to estimate the maximum burial depth of sediments and subsequently calculate exhumation. Our results indicate that the southern Bonaparte Basin went through an average of ∼1.9 km total exhumation from the Permian to the present with a maximum exhumation of ∼2.7 km in the Londonderry High. Vitrinite reflectance data suggest that sediments in the Ashmore Platform were subjected to heat from magmatic events. From the Permian to the Late Triassic, exhumation was confined within the Ashmore Platform (∼0.8 km) and Vulcan Sub-basin. Then from the Late Triassic to the present, exhumation shifted eastwards towards the Londonderry High and Petrel Sub-basin. The results show that the latest Cretaceous and Cenozoic tectonic events produced around 0.8 km of exhumation in the Londonderry High and 0.3 km in the Ashmore Platform. This exhumation likely impeded the formation of Mesozoic petroleum systems in the central Bonaparte Basin while preserving the older Paleozoic system whose hydrocarbons migrated towards traps in around the Londonderry High. Our results indicate porosity values between 20% and 25% for the Vulcan Sub-basin and the Ashmore Platform with little exhumation making them potential areas for CCS. Graphical abstract: Image 1 Highlights: An average of 1.9 km of exhumation occurred in the southern Bonaparte basin since the Palaeozoic. Exhumation impeded the Mesozoic petroleum systems in the central Bonaparte Basin while preserving the older Paleozoic system. Before the Late Triassic, exhumation occurred on the Ashmore Platform, while from the Jurassic, it shifted eastwards to the Londonderry High. The Vulcan Sub-basin and the Ashmore Platform are potential areas for CCS.